An assessment of FIFO and LIFO policies for perishable inventory systems using the system dynamics approach - Ching, Phoebe Lim (Animo Repository, 2019)
This study applied the System Dynamics methodology in evaluating the equilibrium state performance of First-In-First-Out (FIFO) and Last-In-First-Out (LIFO) for perishables. It recognizes that while a certain policy may have optimal results for a few successive periods, it may produce undesirable patterns in the long-term (e.g. accumulation of old stock). A non-perishables scenario was simulated for each policy to validate the logic of the model, and for comparison. This revealed that while FIFO and LIFO have little difference in the long-term for non-perishables, there is a major difference for perishables. Based on the results, this study concludes that LIFO is superior in equilibrium, in terms of consistency in quality of goods sold and stability of production rate. © 2019 IEEE.